Biotransformation of Xylitol Production from Xylose of Lignocellulose Biomass Using Xylose Reductase Enzyme: Review - Azizah, Nurul (Journal of Food and Life Sciences, 2019)
Xylitol is a polyol sugar produced from xylose and has a sweet taste. Xylose can be obtained from hemicellulose in lignocellulosic biomass. The types of lignocellulosic biomass that can be used for the production of xylitol include rice straw, sugarcane bagasse, corn cobs, and corn stover. The process of producing xylitol from xylose can be done by biotransformation using enzymes. One of the enzymes that can be used is xylose reductase. The commonly used microorganisms are the group of Candida genus. The maximum production of xylitol from lignocellulosic biomass is between 12.5 - 96.5 g/L. pH, temperature, substrate concentration, and aeration are parameters that influence the increase in xylitol production. The use of xylose can be used in the food, health and pharmaceutical industries.Keywords: Xylitol, xylose, lignocellulosic biomass, xylose reductase